State-of-the-Art: the quality of case study research in innovation management - Goffin, Keith; Åhlström, Pär; Bianchi, Mattia; Richtnér, Anders (Wiley, 2019)
The practice of innovation management is developing fast. As new concepts emerge, exploratory studies are needed and case study research is often appropriate. To investigate the usage and quality of case study research in innovation management, all of the articles published in five top journals over 20 years (1997–2016) were reviewed. Case study research accounted for 818 of the published articles in this period (12%) and an evaluation template (termed case study evaluation template: CASET) was developed to objectively assess these articles against 10 quality criteria. It was found that the quality of case study research has often been low, although it has improved over time. Similarly, quality was found to fluctuate both within and between the different innovation journals. This indicates that the peer review process for case study research is not as robust as it should be. The assessment of individual articles using the evaluation template found significant deficiencies. Many articles: did not justify why case study research was appropriate; did not apply theoretical sampling criteria; were not transparent on how conclusions were drawn from the data; did not consider validity and reliability adequately; and did not go beyond description in their interpretation. However, the evaluation template also identified 23 “exemplary studies,” which clearly addressed nearly every criterion. Such exemplary studies provide innovation management researchers with “benchmark” reading, which can help shape their own research. This article makes four contributions to the innovation management discipline. First, the evaluation template and exemplary studies can help innovation researchers improve the quality of their case study research. Second, clear recommendations are given for how reviewers can use the template to make the peer review process more consistent and robust. Third, journal editors are encouraged to consider the implications of the findings for their particular journal. Fourth, the article should stimulate a long overdue debate on methodology in innovation management research, including the use of case study research.